Ça roule ! — un pragmatème à décortiquer. Une étude contrastive franco-italienne - Wylecioł, Ryszard; Adamczyk, Karolina (Neophilologica, 2020)
The aim of this paper is to present, after a short introduction to what pragmateme, or pragmatic phraseologism, is and how we understand it as a fixed expressive phrase with affective and emotive load, the results of the Polonium project entitled “Pragmatemes in contrast: from linguistic modeling to lexicographic coding”. In particular, we want to divulgate information concerning analysis of the French pragmateme Ça roule ! and its Italian corresponding phrase A posto!. Furthermore, equivalents of both pragmatemes are also investigated. However, as we consider cognitive linguistics tools as those which may give greater response to what the meaning of pragmatemes is, we broaden the project results with analysis of the trajector-landmark relation and of conceptual metaphors, that are the basis of the imagery for the aforementioned linguistic elements. In this way, we may also try to discern similarities and discrepancies in how close but still different cultures depict the same scene in similar speech events.